El bibliobús: vehículo de información - SANTOS DE PAZ, Lourdes (Revista General de Información y Documentación, 2010)
The need for library services to any place where a local library is difficult to implement, is what fosters the organization of mobile libraries. This article shows the genesis and the various developments that occur in mobile library services in Spain and abroad. Mobile libraries are considered information units as such, just like local libraries are.